2021
DOI: 10.1186/s12917-021-02874-1
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of canine prostate specific esterase, CPSE, at baseline are associated with the relative size of the prostate at three-year follow-up

Abstract: Background Enlargement of the prostate is associated with prostatic diseases in dogs, and an estimation of prostatic size is a central part in the diagnostic workup. Ultrasonography is often the method of choice, but biomarkers constitute an alternative. Canine prostate specific esterase (CPSE) shares many characteristics with human prostate specific antigen (PSA) and is related to prostate size. In men with clinical symptoms of prostatic disease, PSA concentrations are related to prostate grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…An alternative for confirmation of BPH is analysis of serum concentration of the biomarker canine prostate specific esterase (CPSE) biomarker. Serum CPSE concentrations are significantly higher in dogs with BPH than in normal dogs [ 39 41 ]. Our study was conducted on a clinical population of client-owned dogs and the dog owners did not consent to the biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative for confirmation of BPH is analysis of serum concentration of the biomarker canine prostate specific esterase (CPSE) biomarker. Serum CPSE concentrations are significantly higher in dogs with BPH than in normal dogs [ 39 41 ]. Our study was conducted on a clinical population of client-owned dogs and the dog owners did not consent to the biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Another hormone which is nowadays commonly measured in blood serum is canine prostate specific esterase (CPSE) [43,44]. The concentration was reported to be higher in dogs suffering from prostatic diseases [44].…”
Section: Morphological and Hormonal Examinationsmentioning
confidence: 99%
“…Recently, some studies have tried to associate the expression of CPSE with different prostate lesions. Holst et al [ 223 ] evaluated CPSE concentrations in dogs according to prostate volume and found no association of this marker with prostate volume. However, the authors identified an increase in CPSE relative to the basal value of each animal during the follow-up, considering the basal values previously evaluated.…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%
“…However, the authors identified an increase in CPSE relative to the basal value of each animal during the follow-up, considering the basal values previously evaluated. In practice, it would not be a routine assessment to be performed, as there was no association with the patients’ diagnosis [ 223 ]. Moreover, although CPSE presents high concentrations in the seminal fluid, these values are unknown in the different prostate changes in dogs.…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%